Seedlings' Strategy to Overcome a Soil Barrier. (October 2016) - Zhu, Qiang; Benková, Eva
Abstract : The impact of the plant hormone ethylene on seedling development has long been recognized; however, its ecophysiological relevance is unexplored. Three recent studies demonstrate that ethylene is a critical endogenous integrator of various environmental signals including mechanical stress, light, and oxygen availability during seedling germination and growth through the soil.